Saberes pedagógicos para la enseñanza infantil desde la perspectiva de personas educadoras de infantes - Flores Lueg, Carolina; Alvarado Retamal, Tannia; Gutiérrez Oyarce, Tannia Belén; Medel Lilo, Sandra Patricia (Universidad de Costa Rica, 2022)
This article presents the results of a study on the meanings that early childhood educators give to the professional and pedagogical knowledge that sustains their teaching work and gives meaning to their teaching practices. The research it situated from an interpretive paradigm, with a qualitative methodology and the hermeneutical phenomenological method. It was developed in 2020 with the participation of seven educators intentionally included according to defined criteria and their availability, who work in schools located in the Region de Ñuble, Chile. The production technique of information was the semi-structured interview and the data analysis it carried out through a mixed categorization process (deductive and inductive). From the deductive perspective, the central category for the analysis was professional knowledge, and from the inductive perspective, experiential knowledge acquired about teaching and teacher reflection processes. It was considered inter-subjects triangulation as a procedure to validate the information. The main results show that for educators, pedagogical knowledge represents the foundation of their professional identity, whose experiential dimension constitutes the main referential framework on which they emotionally and intuitively resolve teaching situations.